DEMOGRAPHIC POLICY OF FRANCE - L. D. Efanova; K. A. Fedorova (Вестник университета)
Presently, demographic policy is of great importance for solving the problem of depopulation. The article reviews the experience of France in solving this challenge, analyzes the various methods used in this country to deal with population decline. Special attention has been paid to the state support of families and children through the provision of social payments and benefits. Trends and forecasts of demographic processes in France have been considered also, taking into account the measures taken by the state to support the family. Based on the study, conclusions have been made about the effectiveness of demographic policy in France.